Monster bugs - Penner, Lucille Recht; Johnson, Pamela (New York : Random House, 1996)
Describes some of the world's largest insects and spiders, including the Goliath beetle, praying mantis, tarantula, and giant atlas moth.
Keywords: Insects; Insects; Spiders; Spiders; Insects